Strategi Pendidikan Islam di Era Digital - Muh Habibulloh; Himad Ali (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2024)
This study aims to investigate effective Islamic education strategies in the digital era. In the context of globalization and technological advancement, Islamic education needs to face new challenges and harness the potential of digital technology to improve the quality of learning and the application of Islamic values. This abstract presents the background, objectives, research methods, findings and potential implications of this study. The digital age offers various opportunities and challenges in Islamic education. Digital technologies, such as computers, the internet, mobile devices, and social media, have changed the way we learn and interact with knowledge. The purpose of this study was to identify effective Islamic education strategies in the digital era, focusing on the use of technology in enhancing religious understanding, student engagement, and the application of Islamic values in daily life. This research uses a qualitative approach by collecting data through a literature review.